Ethics in management : business and the professions - Boaks, Jacqueline (Research in ethical issues in organizations ;, 2025)
Management and leadership roles in business and professions entail a wide range of ethical issues and challenges. These are apparent to anyone occupying such roles, aspiring to them, or subject to decisions by managers and leaders. Their effects on our daily lives are unavoidable and wide-ranging, never more so than in times of flux and crisis. In response, the authors of the papers in this volume consider angles such as the nature of licence to operate, whether management attracts any kind of moral exceptionalism, and the ethics of 'passion' at work. In addition to this, other topics explored that speak to Research in Ethical Issues in Organizations' broader purpose, including what considerations we should have when doing research for social impact and when we have a duty to intervene to protect others. Ethics in Management: Business and the Professions is essential reading for students across the disciplines of management, business, organizational behaviour, and ethics, policymakers, leaders and managers to gain knowledge of the moral considerations in the workplace, and responsibilities in research and intervention for societal welfare.